Dependent Origination and its Corollaries - Leawprakon, Thawee (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
This research article concerns the Dependent Origination and Corollaries which are related to the Lord Buddha’s Teachings. It definitely concerns to the Law of Karma, the Law of Causation mentioned in the Buddhist Teachings. The four main theories related to the Dependent Origination and Corollaries are, 1) The Law of Karma which is the Law of causality. 2. The theory of Momentariness which refers to the impermanence of every existence. 3. The theory of ‘No-Ego’ which refers to the unimportance of any material substance’. 4. The theory of Causal Efficiency’